Management of post burn hand deformities - Sabapathy S; Bajantri Babu; Bharathi R (Indian Journal of Plastic Surgery)
The hand is ranked among the three most frequent sites of burns scar contracture deformity. One of the major determinants of the quality of life in burns survivors is the functionality of the hands. Burns deformities, although largely preventable, nevertheless do occur when appropriate treatment is not provided in the acute situation or when they are part of a major burns. Reconstructive procedures can greatly improve the function of the hands. Appropriate choice of procedures and timing of surgery followed by supervised physiotherapy can be a boon for a burns survivor.